2010
DOI: 10.1177/112972981001100103
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of an Ethanol/Sodium Citrate Locking Solution on the Mechanical Properties of Hemodialysis Catheters

Abstract: We conclude that the 30% ethanol/4% sodium citrate locking solution had an effect on the mechanical properties of the catheters investigated, but not to the degree that would preclude further in vivo investigation. Further studies are necessary to determine the safety and efficacy of this catheter locking solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…A French study involving critically ill patients with nontunneled catheters compared a 2-minute ethanol dwell time to heparinized controls and did not show a significant difference in outcome. 50,57 The authors suggested that the short interval of catheter use likely contributed to the results as previous positive studies involved longer durations of catheter use.…”
mentioning
confidence: 83%
“…A French study involving critically ill patients with nontunneled catheters compared a 2-minute ethanol dwell time to heparinized controls and did not show a significant difference in outcome. 50,57 The authors suggested that the short interval of catheter use likely contributed to the results as previous positive studies involved longer durations of catheter use.…”
mentioning
confidence: 83%
“…A polyurethane‐like material revealed no morphological abnormalities after immersion for 30 minutes in 60% ethanol solutions; however, there was a significant release of compounds 86 , 87 . Vercaigne et al 88 tested forces required to break hemodialysis catheters. Catheters exposed to ethanol/sodium citrate locking solutions required less force to break compared with saline controls over 12 and 24 weeks.…”
Section: Prevention Strategies—ethanol Lock Therapymentioning
confidence: 99%
“…The reduced ethanol concentration in the GTN lock presents a greater margin of safety from adverse clinical reactions (21), as well as a greater margin of safety from effects on catheter mechanical strength (32). In conclusion, the GTN lock composition reported here merits further in vivo and clinical study to establish its utility in preventing catheter infection or in salvaging infected catheters, based on its reduced ethanol levels, absence of antibiotics, and safe citrate and GTN concentrations.…”
Section: Discussionmentioning
confidence: 99%